A Different Tenor: Glimpses and Critical Reflections: Mission as Companionship: Toward A Theology of Mission for the Diakonia of the United Church of Canada: Toronto Journal of Theology: Vol 25, No 2 - Park, JungHee (Toronto journal of theology, 2009)
Fifty years ago, a young China-born Katharine B. Hockin, a United Church of Canada (UCC) diaconal minister and missionary, reflecting on the harmful implications of "mission to others" through her experience of listening to Chinese Christians and First Nations peoples in Canada, learned that right relations with companions had to start with her own healing, a gift of the spirit received through "listening to others in context," developed her "missiology of companionship." Today, a young Korean-born UCC diaconal minister explores the missiology and mission practice of Katharine B. Hockin and two of her former diaconal students and critiques the missiology of the contemporary scholar Robert J. Schreiter's mission as "healing of others" with that of Marilyn J. Legge's mission as "healing ourselves with others." She finds Hockin's transformation from "mission as healing of others" to "mission as companionship" compellingly appropriate for the diakonia of the UCC today.